Penggunaan Metode ROC dan PROMETHEE II Pada Pemilihan Investasi Sektor Perbankan - Lestari, Tira Ayu Verania; Didi Suhaedi (UPT Publikasi Ilmiah Unisba, 2025)
Abstract. This study focuses on the selection of banking sector investments listed in the LQ45 Index. Investment in the banking sector plays an important role in the economy. However, investors have difficulty in choosing the right company based on the bank's financial health. To help assess a healthy company, various assessment criteria can be set such as Capital Adequacy Rate, Non Performing Loan, Return On Asset, Return On Equity, Net Interest Margin, Operating Costs and Operating Income, and Loan to Deposit Ratio. Meanwhile, to help select investments, this study uses the Rank Order Centroid method to determine the weight value of each criterion and Promethee II to determine the ranking order of alternative investments. The calculation results using the Promethee II method show that alternative Bank 3 (A3) (net flow = 0.27) as the first ranked alternative, Bank 2 (A2) (net flow = 0.24) as the second ranked alternative, Bank 1 (A1) and Bank 7 (A7) (net flow = -0.01) as the third ranked alternative, Bank 5 (A5) (net flow = -0.03) as the fourth ranked alternative, Bank 6 (A6) (net flow = -0.15) as the fifth ranked alternative, and Bank 4 (A4) (net flow = -0.32) as the sixth ranked alternative. Abstrak. Penelitian ini berfokus pada pemilihan investasi sektor perbankan yang terdaftar dalam Indeks LQ45. Investasi dalam sektor perbankan mempunyai peran penting dalam perekonomian. Namun, bagi investor terdapat kesulitan dalam memilih perusahaan yang tepat berdasarkan kondisi kesehatan finansial bank. Untuk membantu menilai perusahaan yang sehat, dapat ditetapkan berbagai kriteria penilaian seperti Capital Adequacy Rate, Non Performing Loan, Return On Asset, Return On Equity, Net Interest Margin, Biaya Operasional dan Pendapatan Operasional, dan Loan to Deposit Ratio. Sedangkan untuk membantu pemilihan investasi, penelitian ini menggunakan metode Rank Order Centroid untuk menentukan nilai bobot dari setiap kriteria dan Promethee II untuk menentukan urutan perankingan alternatif investasi. Hasil perhitungan menggunakan metode Promethee II menunjukkan bahwa alternatif Bank 3 () (net flow = 0,27) sebagai alternatif peringkat pertama, Bank 2 () (net flow = 0,24) sebagai alternatif peringkat kedua, Bank 1 () dan Bank 7 () (net flow = -0,01) sebagai alternatif peringkat ketiga, Bank 5 () (net flow = -0,03) sebagai alternatif peringkat keempat, Bank 6 () (net flow = -0,15) sebagai alternatif peringkat kelima, dan Bank 4 () (net flow = -0,32) sebagai alternatif peringkat keenam.